VISUALISASI OPERASI TRIGONOMETRI (SINUS DAN COSINUS) - Wildatus Sholihah (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2023)
This article discusses a scheme for creating a visual representation of trigonometry and its operations on sine and cosine. This visual representation is then called trigonometric visualisation. The formulas in the visualisation of trigonometric operations apply to all trigonometric identities constructed from sines and cosines with degrees no more than 2. Research was carried out by analyzing trigonometric representations of right triangles from various sources. The results of the research are procedures or techniques for creating trigonometry visualizations of sine and cosine and their operations. Operations in trigonometry visualization are: multiplication, addition, and subtraction of sine and cosine.